2011
DOI: 10.1016/j.ejpain.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased efficacy of early spinal cord stimulation in an animal model of neuropathic pain

Abstract: Although spinal cord stimulation (SCS) is an established treatment for chronic neuropathic pain, pain relief is still not successful in a large group of patients. We suggest that the success of SCS may be related to the timing of SCS during the development of chronic neuropathic pain. We therefore compared the effect of SCS applied after 24h of neuropathic pain (early SCS) and after 16days of neuropathic pain (late SCS). For early SCS, male Sprague-Dawley rats (n=13) were implanted with an SCS device, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 30 publications
1
42
0
1
Order By: Relevance
“…The effects of SCS at higher frequencies are similar to that found in animals with nerve injury. 13,14,[18][19][20]22,23,28,67,76 However, our previous studies show that a lower frequency (4 Hz) also reduced nerve injury-induced pain. 67,69,77 The differences between sensitivity to low-and high-frequency SCS between the models is unclear but could relate to different mechanisms of action of low-and high-frequency SCS, since low-frequency (4 Hz) SCS uses μ-opioid receptors and high-frequency (60 Hz) SCS uses δ-opioid receptors.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The effects of SCS at higher frequencies are similar to that found in animals with nerve injury. 13,14,[18][19][20]22,23,28,67,76 However, our previous studies show that a lower frequency (4 Hz) also reduced nerve injury-induced pain. 67,69,77 The differences between sensitivity to low-and high-frequency SCS between the models is unclear but could relate to different mechanisms of action of low-and high-frequency SCS, since low-frequency (4 Hz) SCS uses μ-opioid receptors and high-frequency (60 Hz) SCS uses δ-opioid receptors.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies show a cumulative and long-lasting (carryover) effect with repeated SCS, 67,68,81 while others show a more short-term effect that lasts for minutes or hours after SCS. 14,23,69,82,83 It is possible that the differences between studies relates to variables of stimulation. Previous studies have routinely delivered SCS at amplitudes of 60% to 70% of motor threshold, 14,23,83 which is similar to that used clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to show the long-term effectiveness of SCS with repeated treatment and to show improvements in physical activity. Prior studies have shown that a single treatment or treatment for 4 -5 days reduces mechanical hyperalgesia of the paw after nerve injury in multiple models (Guan et al, 2010;Maeda et al, 2009;Smits et al, 2006;Song, Ansah, Meyerson, Pertovaara, & Linderoth, 2013;Truin et al, 2011;Sato et al, 2013;Sato et al, 2014). The magnitude of the reduction varies considerably between studies, with some reports showing nearly complete reversal and others showing a smaller reversal.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a rat model of neuropathic pain, significant improvements in mechanical allodynia were appreciated in rats that received early SCS. 26 Although neuropathic pain models suggest that central sensitization occurs early after injury via a time-dependent glutamatergic and GABAergic mechanism, proximity of neuromodulatory therapy to the time of injury may be essential for efficacy and possible long-term outcome. 26,27 In our population, young, highly functional soldiers are exposed to unique combat injuries.…”
Section: Discussionmentioning
confidence: 99%